2009
DOI: 10.1002/uog.6427
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial tissue Doppler assessment of diastolic function in the growth‐restricted fetus

Abstract: Objectives Myocardial tissue Doppler (MTD) is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
39
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 20 publications
6
39
1
1
Order By: Relevance
“…A similar study was undertaken by Naujorks et al where the results obtained were comparable to the present study. 6 A paradoxical finding in the present study which is not in accordance with the present literature is the finding of lower MPI' in IUGR babies in comparison to normal babies. All other studies show a higher value in IUGR babies explained by decreased stiffness of myocardial tissue in normal growth babies not seen in IUGR babies with increasing gestational age.…”
Section: Discussioncontrasting
confidence: 99%
“…A similar study was undertaken by Naujorks et al where the results obtained were comparable to the present study. 6 A paradoxical finding in the present study which is not in accordance with the present literature is the finding of lower MPI' in IUGR babies in comparison to normal babies. All other studies show a higher value in IUGR babies explained by decreased stiffness of myocardial tissue in normal growth babies not seen in IUGR babies with increasing gestational age.…”
Section: Discussioncontrasting
confidence: 99%
“…12,18 In contrast with conventional ultrasound measurements, we observed differences in the TDI diastolic velocities parameters in the series of fetuses with IUGR included in this analysis as compared to values recorded in literature for fetuses from normal pregnancies. Our findings are similar to those reported by Naujorks et al, 3 which observed higher values of the E/A ratios at the interventricular septum in a group of IUGR fetuses with placental insufficiency as compared with appropriate for gestationalage fetuses from normal mothers. In contrast, other studies did not shown significant differences in TDI measurements in IUGR fetuses defined only by reduced weight or found similar TDI measurements in fetuses coming from healthy pregnancies and IUGR affected fetuses.…”
supporting
confidence: 92%
“…These findings are in line with those reported in other studies. 3,4,7 However, reduced or increased E/A ratios have also been reported. 10,11 The lack of significant differences in our study may be explained by the inclusion of only two cases with an umbilical artery reverse flow pattern as an indirect marker of an advanced fetal heart distress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations